Diagnostic significance of complete blood count in cardiovascular patients; Samara State Medical University - A. M. Chaulin; Yu. V. Grigorieva; T. V. Pavlova; D. V. Duplyakov (Российский кардиологический журнал)
This article discusses the relationship between parameters of complete blood count (CBC) and cardiovascular diseases (CVD). The main advantages of CBC over other methods of CVD diagnostics are low cost and wide availability. At the same time, the low specificity of CBC is an important disadvantage, limiting its diagnostic value.After analyzing the results of numerous clinical studies, we concluded that the most important CBC are red cell distribution width, mean platelet volume, total leukocyte count, neutrophil to lymphocyte ratio, platelet-to-lymphocyte ratio, monocyte to high-density lipoprotein ratio. We discuss the diagnostic value of each of the above indicators in CVD. Careful attention to these parameters by clinicians can, to a certain extent, improve the therapeutic and diagnostic process in patients with CVD.